2023
DOI: 10.3390/foods12122345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Policy Intervention on Food System Resilience to Emergency Risk Shock: Experience from China during COVID-19 Pandemic

Abstract: Achieving the goal of zero hunger within the goal of sustainable development requires improving the resilience of food systems to various types of risk shocks; food systems have shown significant vulnerability to COVID-19 outbreaks and transmission. By analyzing the impact of China’s lockdown policy and food security emergency policy in 2020 on food prices during the COVID-19 pandemic, we can clarify the role of policy intervention in enhancing the resilience of the food system, which can provide guidance, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Collective purchases and guaranteed supply companies based on e-commerce platforms also ensured the traceability and visibility of the food supply. Furthermore, implementing transportation policies and establishing joint supply emergency systems in major production and consumption areas have been proven to play a significant positive role in stabilizing food prices (Cui et al, 2023). Lastly, the collaborative efforts between communities and volunteers ensure minimal contact and efficient food delivery.…”
Section: Systemic Coherence and Efficiencymentioning
confidence: 99%
“…Collective purchases and guaranteed supply companies based on e-commerce platforms also ensured the traceability and visibility of the food supply. Furthermore, implementing transportation policies and establishing joint supply emergency systems in major production and consumption areas have been proven to play a significant positive role in stabilizing food prices (Cui et al, 2023). Lastly, the collaborative efforts between communities and volunteers ensure minimal contact and efficient food delivery.…”
Section: Systemic Coherence and Efficiencymentioning
confidence: 99%
“…Secondly, scholars have focused on the impact of external shock factors on the pork price. Studies have found that pig epidemics diseases (e.g., blue-ear disease, acute diarrhea epidemic, swine foot-and-mouth disease, and African swine fever) [13][14][15][16], government policies [17,18], inflation [19], the consumer price index (CPI) [20], and network attention [21,22] can also have positive or negative impacts on the pork price. To sum up, due to the different research perspectives, selected factors, and sample sizes, there is still a lack of consistent conclusions regarding the impact of these shocks.…”
Section: Introductionmentioning
confidence: 99%